Women of the post - Sanders, Joshunda (Park Row Books, 2023)
In 1944, four friends, part of the only unit of Black women to serve overseas in World War II, work tirelessly to reunite soldiers with their loved ones through the letters they write and find things taking a personal turn when a backlogged letter upends their lives.